MODEL PEMBINAAN ‘IN-HOUSE TRAINING’ SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM PENELITIAN DAN PENULISAN KARYA ILMIAH - Dharmawan, K.; Ramona, Y.; Rupiasi, N. N. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
Various attempts have been made by the government to improve the quality of teachers and quality of education, such as allowances certification, training or the opportunity to continue to pursue education to Master degree. However, these efforts have not able to improve the ability of research as mandated in the Minister Regulation PAN No. 16 Year 2009 Clause 11 that concerning the obligation of teachers in scientific publications. To assist teachers in implementing the mandate, it is necessary to develop a model of coaching so that teachers can improve their competence and /or teacher professionalism in research. In this paper, it is developed model guidance for teachers in improving the professionalism of teachers in research. The method used in the development of this coaching model is a method of in-house training, the coaching done by setting their respective schools, where teachers implement instructional programs. This paper is the result of the program community service activities are funded by DIKTI in the scheme of science and technology for society that was summarized in the form of coaching model through in-house training which consists of three stages approaches, namely scientific, competence, and publications. The results of this development showed a significant increase, approximately 30% on a teacher's ability to perform research of class action.
Keywords: In-house training; coaching model; professional; research of class action; competency